ANALYSIS OF THE EFFECTIVENESS OF THE COMPLEX OF SURGICAL METHODS FOR THE TREATMENT OF ACUTE CALCULOUS CHOLECYSTITIS IN ELDERLY AND SENILE PATIENTS - Khamdamov, B.Z.; Khaidarov, F.N. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2022)
The nature of the complex surgical treatment of acute calculous cholecystitis in elderly and senile patients, under the conditions of gradation age analysis, made it possible to identify a number of theoretical patterns. Firstly, it is the dependence of the degree of complexity of surgical intervention on the severity of the course of acute calculous cholecystitis. In most cases, it is not reliable. Secondly, this peak value in this rank was presented among patients with moderate severity of acute calculous cholecystitis. Thirdly, the ranking of patients in this subgroup between mild and severe severity of the course of the disease does not allow achieving compliance with the planned type of surgical intervention. This is confirmed by a high level of conversion cases and an increase in the share of the degree of complexity. It seems to us that confirmation of this conclusion is possible only under the condition of an objective assessment of the results of the complex of surgical methods for the treatment of acute calculous cholecystitis in elderly and senile patients. In particular, the analysis of complications and mortality in this category of patients is of interest.